Surgical management of intramedullary spinal ependymomas Abordagem cirúrgica dos ependimomas intramedulares - Andrei Fernandes Joaquim; Marcos Juliano dos Santos; Hélder Tedeschi (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Spinal intramedullary ependymoma is a rare disease with a wide range of clinical presentation, generally requiring surgical treatment. OBJECTIVE: Report our experience and present our surgical technique to achieve total resection and cure. METHOD: We present 12 consecutive cases of intramedullary ependymomas operated between 2000 and 2008 by the senior author (HT). The functional scale proposed by McCormick was used to evaluate the patients' neurological status. RESULTS: Age at presentation varied from 18 to 55 (average 36) years. All tumors had a benign histology. Four (33%) patients were male and eight (67%) were female. According to the site of presentation, six (50%) were localized at the cervical region (including two at the cervicomedullary junction, two at the cervico-thoracic junction and two exclusively at the cervical level), four at the thoracic level and two at the conus/ cauda equina. Dyshestesia was a common finding at the neurological exam in eight patients (67%). Total resection was achieved in all cases. Six patients showed neurological improvement postoperatively, whereas the other six remained stable. CONCLUSION: Adequate knowledge of anatomy and the correct use of microsurgical techniques allowed total resection of these tumors with minimal morbidity and maximum functional recovery. INTRODUÇÃO: Os ependimomas intramedulares são lesões raramente encontradas na prática neurocirúrgica, tendo apresentação clínica variada, geralmente requerendo tratamento cirúrgico. OBJETIVO: Relatar nossa experiência e discutir a técnica microcirúrgica para a ressecção total e conseqüente cura destas lesões. MÉTODO: Apresentamos uma série de 12 casos de ependimomas intramedulares operados sucessivamente entre 2000 e 2008 pelo autor sênior (HT). A evolução neurológica foi avaliada através da classificação funcional de McCormick. RESULTADOS: A idade dos pacientes variou de 18 a 55 anos (média de 36 anos). Todos eram histologicamente benignos. Quatro (33%) eram do sexo masculino e oito do feminino (67%). A localização das lesões esteve distribuída da seguinte forma: seis casos (50%) na região cervical (sendo dois na transição cérvico-bulbar, dois na região cérvico-torácica e dois na região cervical isoladamente), quatro na região torácica e dois no nível do conus-cauda-eqüina. Disestesias estavam presentes em oito pacientes no pré-operatório (67% dos casos). A ressecção total foi atingida em todos os casos. Em seis casos (50%), houve melhora dos sintomas neurológicos, enquanto que nos outros seis houve manutenção do quadro clínico. CONCLUSÃO: O conhecimento anatômico e de técnicas microcirúrgicas adequadas permite a ressecção total destas lesões propiciando a cura da doença com mínima morbidade e máxima recuperação funcional.